Can Democracy Survive AI? - Gina Neff (Sociologica)
This essay examines the fundamental tension between artificial intelligence technologies and democratic governance, arguing that AI’s inherent tendencies toward centralization and control pose significant challenges to democratic societies. Drawing on science and technology studies and critical analyses of technological politics, I argue that current AI implementations embody four key anti-democratic characteristics: they represent powerful technologies of centralization and control; they fuel ideologies of unchecked economic growth; they prioritize efficiency over accountability; and they enable absolute control coupled with unaccountable power. The analysis synthesizes historical parallels between computing and control, contemporary developments in AI infrastructure, and emerging policy frameworks to demonstrate how AI’s technical architecture and commercial implementation systematically undermine democratic values of transparency, accountability, and public participation. Through examination of recent political developments and corporate practices, the essay reveals how AI’s centralization of power and erosion of public oversight threaten democratic institutions. I conclude that democracy’s survival in an AI-driven future depends on reimagining and rebuilding digital technologies with democratic accountability at their core, requiring new frameworks for public oversight and corporate governance.